A comparative study of modified cotton biochar and activated carbon based catalysts in low temperature SCR. (15th September 2015) - Shen, Boxiong; Chen, Jianhong; Yue, Shiji; Li, Guoliang
Graphical abstract: Highlights: MnCeO x /biochar by co-activation (COA) exhibited a higher specific surface area. MnCeO x /biochar (COA) exhibited a higher surface acidity. The Mn 4+ /Mn 3+ ratio was higher in MnCeO x /biochar (COA). More adsorbed oxygen is present in MnCeO x /biochar (COA). MnCeO x /biochar (COA) demonstrated a higher selective catalytic reduction activity. Abstract: A series of MnCeO x -based catalysts loaded on modified cotton biochars and commercial activated carbon were studied to investigate the selective catalytic reduction (SCR) of NO at low temperatures. The physicochemical properties of these catalysts were investigated by a variety of characterization methods. The results indicated that the co-activated cotton biochar may be a potential material for use as a low temperature SCR catalytic support instead of the commercial activated carbon (AC). MnCeO x /biochar by co-activation (COA) exhibited a higher specific surface area, surface acidity and a Mn 4+ /Mn 3+ ratio than the other catalysts. The XRD analysis indicated that MnCeO x was more dispersed on the surface of the cotton biochar (COA) than the other supports. In addition, there were more adsorbed oxygen species and oxygen functional groups on the surfaces of the MnCeO x /biochar (COA) catalysts. These properties of MnCeO x /biochar (COA) assisted the SCR reaction and the N2 selectivity. Moreover, the rich adsorbed oxygen species and oxygen functional groups on the surfaces of the MnCeO x /biochar (COA) catalyst promoted the oxidation of NO to NO2, which resulted in high SCR activity.